2013
DOI: 10.1002/clc.22182
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Frailty and Functional Status on Outcomes in Elderly Patients With ST‐Segment Elevation Myocardial Infarction Undergoing Primary Angioplasty: Rationale and Design of the IFFANIAM Study

Abstract: The IFFANIAM study (Impact of frailty and functional status in elderly patients with ST segment elevation myocardial infarction undergoing primary angioplasty) is an observational multicenter registry to assess the impact of frailty and functional status on outcomes of elderly patients with ST-segment elevation myocardial infarction (STEMI) undergoing primary angioplasty. STEMI patients age 75 years or older undergoing primary angioplasty will be extensively studied during admission in 4 tertiary care Hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
5

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 34 publications
0
12
0
5
Order By: Relevance
“…Frailty is an age‐associated biological syndrome characterized by a decline in overall function or biological reserve and response to situations that require rapid adaptive responses, resulting from the deterioration of multiple physiological systems. Frailty frequently coexists with cardiovascular diseases . Other studies have described that frailty is associated with increased mortality and health care utilization among community patients with HF, but its influence in prognosis after HF hospitalization is less well known.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Frailty is an age‐associated biological syndrome characterized by a decline in overall function or biological reserve and response to situations that require rapid adaptive responses, resulting from the deterioration of multiple physiological systems. Frailty frequently coexists with cardiovascular diseases . Other studies have described that frailty is associated with increased mortality and health care utilization among community patients with HF, but its influence in prognosis after HF hospitalization is less well known.…”
Section: Discussionmentioning
confidence: 99%
“…Frailty frequently coexists with cardiovascular diseases. 45,46 Other studies have described that frailty is associated with increased mortality and health care utilization among community patients with HF, 12,47,48 but its influence in prognosis after HF hospitalization is less well known.…”
Section: Discussionmentioning
confidence: 99%
“…An observational multicenter registry to assess the clinical impact of frailty in the elderly patients with STEMI has been planned. 20 A result of the study may bring any findings in the geriatrics field.…”
Section: Prognostic Impact Of the Barthel Index On Admission And Critmentioning
confidence: 97%
“…They concluded that frailty status was an independent predictor of in-hospital mortality in this population. Other studies have been designed in STEMI but have not been published yet [16]. Several studies also suggest an association between frailty status and in-hospital mortality [17, 18].…”
Section: Discussionmentioning
confidence: 99%